Synthesis and Characterization of Some Mixed-Ligand Complexes Containing N-Acetyl Tryptophan and Î±Picoline with Some Metal Salts - Sarhan, B. M.; Waheed, E. J.; Naema, B. Z. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Some metal ions (Mn+2, Fe+2, Co+2,Ni+2,Cu+2 and Cd+2) complexes of N-acetyl Tryptophan (AcetrpH) and Î±-Picoline (Î±-Pic) have been synthesized and characterized on the basis of their FTIR,UV-Vis spectroscopy , conductivety measurements , magnetic susceptibility. From the results obtained, the following general formula has suggested for the prepared complexes. [M+2(Acetrp)2(Î±-Pic)2]. XH2O Where M = Mn+2, Fe+2, Co+2,Ni+2,Cu+2 and Cd+2 X = 0 , 0 , 5 , 2 , 1 , and 0 (Acetrp)- = Ligand ion(N-acetyl Tryptophanato) (Î±-Pic) =Î±-Picoline